2004
DOI: 10.1079/nrr200478
|View full text |Cite
|
Sign up to set email alerts
|

Age-associated B vitamin deficiency as a determinant of chronic diseases

Abstract: The number of elderly individuals is growing rapidly worldwide and degenerative diseases constitute an increasing problem in terms of both public health and cost. Nutrition plays a role in the ageing process and there has been intensive research during the last decade on B vitaminrelated risk factors in vascular and neurological diseases and cancers. Data from epidemiological studies indicate that subclinical deficiency in most water-soluble B vitamins may occur gradually during ageing, possibly due to environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 131 publications
3
21
1
1
Order By: Relevance
“…Extensive research in the last decade has suggested that subtle deficiencies in B vitamins may be risk factors for vascular and neurological diseases and cancers (Brachet et al, 2004). Thus, a combined deficiency of folate and vitamin B12 is associated with neuropsychiatric disorders among the elderly, e.g., development of dementia and Alzheimer's disease (Seshadri et al, 2002).…”
Section: Vitaminsmentioning
confidence: 99%
“…Extensive research in the last decade has suggested that subtle deficiencies in B vitamins may be risk factors for vascular and neurological diseases and cancers (Brachet et al, 2004). Thus, a combined deficiency of folate and vitamin B12 is associated with neuropsychiatric disorders among the elderly, e.g., development of dementia and Alzheimer's disease (Seshadri et al, 2002).…”
Section: Vitaminsmentioning
confidence: 99%
“…Deficiencies in any of these B-vitamins can perturb the complex regulatory network maintaining one-carbon metabolism resulting in reduced methylation status within the relevant tissue, hyperhomocysteinemia, and/or increased misincorporation of uracil into DNA as a result of thymidylate synthesis being impaired owing to low 5,10-methylene-THF concentrations and thus uracil is inserted instead during DNA synthesis which in turn may contribute to adverse health outcomes in ageing [11,12]. In addition, genetic polymorphisms, including the common 677 C → T polymorphism in the gene encoding the folate-metabolising enzyme MTHFR, can interact adversely with sub-optimal status of one or more of the B-vitamins in one-carbon metabolism and thus contribute to a greater disease risk [13].…”
Section: Metabolic Role Of B-vitamins In One-carbon Metabolismmentioning
confidence: 99%
“…Except pregnant and lactating women, the minimum folate requirement for adults has been estimated at 50 μg.day −1 (Crittenden et al 2003). In addition, dietary intake of 400-600 μg.day −1 is commonly recommended for pregnant women (Allen 2003;Brachet et al 2004;Crittenden et al 2003;Laiño et al 2013).…”
Section: Nutritional and Health Aspectsmentioning
confidence: 99%